Investigasi Dampak Brand Ambassador dan Mutu Produk pada Keputusan Beli - Elizabeth (Jurnal EMT KITA, 2025)
The purpose of this research is to examine the impact of brand ambassadors and product quality on purchasing decisions for Uniqlo products at the Tiktok store. This study uses a quantitative method with regression analysis. The sampling method applies a purposive sampling technique and the number of samples is 85 respondents obtained by distributing questionnaires to Tiktok users in Indonesia via Google form. Structural Equation Modeling-Partial Least Squares (SEM-PLS) is used in analyzing the data. The results of this study indicate that brand ambassadors and product quality positively and significantly influence purchasing decisions. Meanwhile, price does not have a significant effect on purchasing decisions for Uniqlo products at the Tiktok store.
Keywords: Purchase Decision; Brand Ambassador; Product Quality